Smartphones: a menace to the eye-fact or fiction? - Abdul Rahim, Muhammad Afzam Shah; Purslow, Christine; Buckhurst, Phillip J; Buckhurst, Hetal D (Wiley Online Library, 2014)
Background:Smartphones were first introduced in 1993. Over the last 20 years, smartphones have become pivotal in our daily lives as they allow us to view e-mails, browse websites and even function as a mobile entertainment device. Smartphones are mainly used at close working distances and research by Bababekova et al. (2013) suggest that these working distances differ significantly from those when reading hardcopy text. As such, it is anticipated that these differences could lead to an excessive demand such as grittiness, dry eyes and tired eyes/visual fatigue.Purpose:It is still unclear as to what impact, if any, smartphones have on visual function and therefore a review was conducted to assess the current literature. The literature review focuses on the key visual outcomes that include tear stability, dry eyes, blinking rates, aperture size, visual fatigue, accommodation and intraocular pressure.Method:Publications pertaining to smartphones and the effect on visual functions were reviewed via online database PubMed, Science-Direct, Google Scholar, Medline and Web of Sciences. Keywords used for the search include smartphones, tear stability, dry eye, blinking rates, palpebral aperture size, visual fatigue, accommodation and intra-ocular pressure. The period of database search was conducted from1993 until 10th May 2014.Results:The results demonstrated a paucity of literature on smart-phones and the effect on visual functions. The few studies featured in the literature review are qualitative methodologies (Moon et al., 2014)with no measure of the visual functions of interest (Bababekova et al.,2013). These studies concluded that smartphones are on important risk factor for dry eyes in children (Moon et al., 2014) and that the working distances for smartphones were closer than the typical near working distances of 40 cm for adults when compared to viewing hardcopy text (Bababekova et al., 2013). Conclusions:Due to the scarcity of experimental evidence, it is currently unclear what level of impact smartphones have on visual function/system. Despite this, the literature suggests that there are many areas that require further investigation. In particular, future research should investigate correlates of dry eyes and visual fatigue by assessing tear stability, blinking rates, aperture size, accommodation and intraocular pressure. It is anticipated that the findings of this research will aid Optometrists in managing patients who may be suffering from the potential effects of smartphones use. Moreover, this could also have implications for ergonomic design of smartphones in the future.